2015
DOI: 10.1017/ppr.2015.17
|View full text |Cite
|
Sign up to set email alerts
|

Connected Histories: the Dynamics of Bronze Age Interaction and Trade 1500–1100bc

Abstract: The Bronze Age was the first epoch in which societies became irreversibly linked in their co-dependence on ores and metallurgical skills that were unevenly distributed in geographical space. Access to these critical resources was secured not only via long-distance physical trade routes, making use of landscape features such as river networks, as well as built roads, but also by creating immaterial social networks, consisting of interpersonal relations and diplomatic alliances, established and maintained throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 48 publications
(62 reference statements)
1
36
0
1
Order By: Relevance
“…Definitions of Frattesina as a ‘central place’, ‘primary node’, ‘port of trade’ or ‘ emporium ’ recur frequently in the scholarly literature (e.g. Pearce 2000; Bietti Sestieri 2008; Harding 2013; Kristiansen & Suchowska-Ducke 2015).
Figure 1.Aerial photograph of the Frattesina site (courtesy of the Regione Veneto website: ).
…”
Section: Frattesina: Between the Mediterranean And Central Europementioning
confidence: 99%
“…Definitions of Frattesina as a ‘central place’, ‘primary node’, ‘port of trade’ or ‘ emporium ’ recur frequently in the scholarly literature (e.g. Pearce 2000; Bietti Sestieri 2008; Harding 2013; Kristiansen & Suchowska-Ducke 2015).
Figure 1.Aerial photograph of the Frattesina site (courtesy of the Regione Veneto website: ).
…”
Section: Frattesina: Between the Mediterranean And Central Europementioning
confidence: 99%
“…Recent provenance investigations, applying new chemical protocols based on the strontium isotopic tracing system, indicate that skin and textile raw materials were traded during the Nordic Bronze Age (1700-500 BC) (Frei et al 2015a & b). The term 'trade' instead of 'exchange' is used here following terminology recently adopted for provenance analyses of Scandinavian metal artefacts and glass beads from the Nordic Bronze Age (Ling et al 2014;Kristiansen & Suchowska-Ducke 2015;Varberg et al 2015). The most recent example of wool provenance investigation is the study of the Danish Bronze Age elite female grave from Egtved, which demonstrated that the clothing was made of non-local wool (Frei et al 2015a).…”
Section: Researchmentioning
confidence: 99%
“…At the core of this long-standing debate is the relationship between European Bronze Age metals and societies, which consequently have been the subject of much scholarship, especially as metals can be used as a proxy for populations, trade systems, conflict, religious practices, and institutional dynamics. Emphasis continues to be placed on the multiple connections between metal objects, metal trade, and elites (e.g., Earle et al 2015;Kristiansen and Suchowska-Ducke 2015;Vandkilde et al 2015).…”
Section: Identifying the Key Issues For The European Bronze Agementioning
confidence: 99%
“…Fourthly, the development of use-wear analyses on Bronze Age objects is starting to see more widespread application as are better recording systems, fewer untested assumptions, and a greater awareness of the complexities of interpretations (see Dolfini and Crellin 2016;Gutiérrez-Sáez and Martín-Lerma 2015;Horn 2013;Kristiansen 1978Kristiansen , 1984Kristiansen , 2002Kristiansen and Suchowska-Ducke 2015;Kuijpers 2017Kuijpers , 2018Molloy 2008Molloy , 2009Molloy , 2010Molloy et al 2016;Roberts and Ottaway 2003;Uckelmann and Mödlinger 2011). What is required is an approach to analyzing and understanding Bronze Age metal circulation and use that can evaluate and further advance the established models and interpretations based on morphologies, typologies, and distributions of Bronze Age copper and bronze objects throughout Europe.…”
Section: What Do We Know About Metal Circulation and Use In European mentioning
confidence: 99%
See 1 more Smart Citation